Does Exchange Rate Devaluation Affect Agricultural Output? Evidence from Nigeria - Olubukoye Opeyemi Oye; Adedoyin Isola Lawal; Ann Eneogu; Joseph IseOlorunkanmi (Binus Business Review, 2018)
The purpose of this research was to examine the effect of exchange rate devaluation on agricultural output in Nigeria. This investigation used the available time series data of 30 years (1986-2016) from the Central Bank of Nigeria (CBN) Statistical Bulletin and the National Bureau of Statistics. Moreover, the real effective exchange rate was used as the proxy for currency devaluation and Consumer Price Index (CPI) was used as a proxy for inflation. Other variables were Agricultural Gross Domestic Product (AGDP), Price of Export (PEXP), and Real Agricultural Exports (RAEXP). The research through the Augmented Dickey Fuller (ADF) and Philip Perron’s unit root tests find that the variables used in the model are integrated in the same order. Using the Johansen’s cointegration test results show that the variables are cointegrated. The results of the Vector Error Correction Model (VECM) indicates that a percent increase in the Real Effective Exchange Rate (REER), a proxy for devaluation. It will lead to a decrease in gross agricultural output. This implies that total agricultural output responds negatively to exchange rate devaluation. The result of the causality test by Toda and Yamamoto reveals that a unidirectional causality exists between real effective exchange rate and price of exports. This shows that a significant relationship exists between exchange rate devaluation and gross exports earnings. It reveals that the past values of the price of exports can be used to predict the current values of agricultural output.